OR33-3 Salt Inducible Kinase is a Negative Regulator of FSH in Ovarian Granulosa Cells - Armouti, Marah (J Endocr Soc, 2019)
Ovulation is the pinnacle of folliculogenesis, a process requiring granulosa cell (GC) proliferation and differentiation to form preovulatory follicles. In human and rodent GCs, we discovered that pituitary follicle-stimulating hormone (FSH) and insulin-like growth factors (IGFs) have interdependent effects on GC differentiation, converging on the activation of the serine/threonine kinase AKT. However, the AKT-controlled mechanisms involved in GC differentiation remain unclear. Here, we examined the role of salt-inducible kinases (SIKs), a known target of AKT, on the stimulation of GC differentiation by FSH. We first examined the expression of the three SIK isoforms in ovarian human and rat GCs and observed that SIK1 is expressed at low levels. In contrast, SIK2 and SIK3 are highly expressed with SIK3 being the strongest. Immunofluorescence of rat GCs and immunohistochemistry of rat ovaries reveal that all SIK isoforms are expressed in the GCs at levels that correlated with the mRNA levels for each isoform (SIK3>SIK2>SIK1). To determine if SIKs play any role in the response of GCs to FSH, we treated rat and human GCs with four different and specific inhibitors of SIK activity. We observed that SIK inhibition potentiated the stimulatory effect of FSH on aromatase mRNA expression, a marker of GC differentiation. This effect was also observed on aromatase protein expression and on the production of estradiol (E2). Thus, E2 levels in cells treated with FSH and SIK inhibitors were significantly higher than treatment with FSH alone. Next, to investigate whether SIK inhibition affects the transcription of the aromatase gene, we transfected rat and human primary GCs with an empty luciferase reporter or a reporter carrying the aromatase promoter. We observed that aromatase promoter activity was significantly higher in cells treated with FSH and SIK inhibitors than FSH alone. Since FSH requires the presence of the IGF1R to activate AKT, we measured SIK expression in GC-specific IGF1R knockout mice and observed that all SIK isoforms are expressed at significantly higher levels when compared to control mice, suggesting that the IGF1R is involved in repressing SIK expression. Moreover, in vivo administration of a SIK inhibitor was able to recover FSH responsiveness in GC-specific IGF1R knockout mice. These findings demonstrate for the first time the involvement of SIK in the regulation of GC differentiation and contribute to our understanding of the mechanisms regulated by FSH and IGFs in the control of aromatase expression.